The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3174/ajnr.a2242
|View full text |Cite
|
Sign up to set email alerts
|

A Transverse and Longitudinal MR Imaging Voxel-Based Morphometry Study in Patients with Primary Cervical Dystonia

Abstract: BACKGROUND AND PURPOSE:Findings of standard MR imaging examinations are usually normal in primary CD. These findings are now increasingly challenged by studies using advanced neuroimaging techniques detecting abnormalities in brain areas that may be functionally involved in the pathophysiology of CD. Our purpose was to evaluate GM volumes in patients with CD at baseline and 5 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 29 publications
7
61
2
3
Order By: Relevance
“…Nine studies [12,[14][15][16][22][23][24][25][26], reporting 11 PFD-HC comparisons (five comparisons of idiopathic cervical dystonia and HC, three of primary blepharospasm and HC, and three of focal hand dystonia and HC) comprising 199 patients and 247 HC with females 116 and 143 respectively, met the inclusion criteria for the ALE meta-analysis. The main characteristics of the included populations were presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies [12,[14][15][16][22][23][24][25][26], reporting 11 PFD-HC comparisons (five comparisons of idiopathic cervical dystonia and HC, three of primary blepharospasm and HC, and three of focal hand dystonia and HC) comprising 199 patients and 247 HC with females 116 and 143 respectively, met the inclusion criteria for the ALE meta-analysis. The main characteristics of the included populations were presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of these publications contain inconsistent and controversial results on account of small and heterogeneous samples of participants, as well as substantial methodological differences between studies. For example, some studies found that PFD patients have greater putamen compared with control subjects [12][13][14]; however, some other studies detected smaller putamen in PFD patients [15,16]. Hence, there has been an increasing interest in using metaanalysis to identify consistent results of VBM findings in PFD.…”
Section: Introductionmentioning
confidence: 91%
“…Putamen is the motor part of the striatum. Volume changes in putamen have been illustrated in numerous studies concerning primary dystonia [41][42][43][44]. The motor regions work cooperatively on movement planning and execution, sending projections to the corresponding parts of putamen [45].…”
Section: Discussionmentioning
confidence: 98%
“…Studies using voxel-based morphometry (VBM) reported alterations in gray matter (GM) volume in the basal ganglia (Draganski et al, 2003;Pantano et al, 2011;Prell et al, 2013), the cortical motor circuitry (Draganski et al, 2003;Pantano et al, 2011;Prell et al, 2013), and the cerebellum in CD (Draganski et al, 2003;Prell et al, 2013). Despite several reports on structural differences between dystonia patients and healthy controls at baseline, few studies exist on longitudinal structural changes.…”
Section: Introductionmentioning
confidence: 96%
“…Regional GM alterations have been demonstrated in several movement disorders. VBM has also been of value in the identification of longitudinal GM alterations in neurological diseases, reflecting for example disease progression or treatment response (Pantano et al, 2011). In this study, we tested the hypothesis that BoNT treatment modifies the 'dystonic brain', by evaluating wholebrain GM volume (GMV) by means of VBM methodology in a longitudinal pre-and post-treatment design within CD patients.…”
Section: Introductionmentioning
confidence: 99%